The Network of Causal Constructions in the Diachrony of Portuguese (Revista de Estudos da Linguagem, 2024)
Diachronic Construction Grammar has been consolidated in the most recent studies as an approach that allows explaining both the emergence and disappearance of constructions as well as the changes in the links between the various constructions of a network. Based on this theoretical perspective, we focus on the network of causal constructions over the archaic, classic and modern Portuguese. Our main goal is to identify changes in the links between the different causal constructions. We took as an analysis vector the domain of the causal relation (content, epistemic, and speech acts). The analysis of the distribution of causal constructions according to the type of causal link they instantiate allowed to verify not only a quite different distribution of causal constructions over the centuries, but also significant changes in the greater or lesser centrality of each of them in one or another domain, indicating expansion or specialization of use throughout its evolution.